1979
DOI: 10.1111/j.1365-2125.1979.tb00896.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ageing on the hepatic clearance of propranolol.

Abstract: 1. Plasma propranolol concentrations were measured in healthy old and young subjects following single oral doses of 40 mg, single i.v. infusions of 0.15 mg kg‐1 and after nine 40 mg oral doses given four times daily. 2. In each of the three studies, the elderly had higher plasma propranolol concentrations than the young despite having similar apparent volumes of distribution. 3. The terminal half‐life of propranolol was similar in the two groups after oral propranolol but significantly shorter in the young aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1

Year Published

1981
1981
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(44 citation statements)
references
References 26 publications
2
41
1
Order By: Relevance
“…Such a reduction has been clearly demonstrated in animals (Kato & Tanaka, 1968) and studies in man have confirmed a reduction in liver size and the number of functioning liver cells with increasing age (Sato et 1970). In the elderly, the decreased plasma clearance of antipyrine (O'Malley et al, 1979) and propranolol (Castleden & George, 1979), have been attributed to a lower rate of metabolism. They all share, with trazodone, a common route of elimination; hydroxylation.…”
Section: Discussionmentioning
confidence: 99%
“…Such a reduction has been clearly demonstrated in animals (Kato & Tanaka, 1968) and studies in man have confirmed a reduction in liver size and the number of functioning liver cells with increasing age (Sato et 1970). In the elderly, the decreased plasma clearance of antipyrine (O'Malley et al, 1979) and propranolol (Castleden & George, 1979), have been attributed to a lower rate of metabolism. They all share, with trazodone, a common route of elimination; hydroxylation.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic studies in the elderly have been performed using intravenous administration with only a few drugs including antipyrine (O'Malley etal., 1971) phenytoin (Hayes, Langman & Short, 1975) diazepam (Klotz et al, 1975), chlordiazepoxide (Roberts et al, 1978), propranolol (Castleden & George, 1979), chlormethiazole and lignocaine (Triggs, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…phenytoin (Houghton, Richens & Leighton, 1975), imipramine and amitriptyline (Nies et al, 1977). This effect of age on plasma drug steady state concentration will be most obvious with drugs such as propranolol which are extensively metabolised by the liver and there is evidence (Castleden & George, 1979) that the elimination of propranolol is reduced in elderly subjects. The hepatic metabolism of some drugs may be increased in hyperthyroidism (Eichelbaum, 1976) and it is also known that smoking, probably through hepatic enzyme induction (Vestel et al, 1975) increases the rate of elimination of certain drugs and may thus be a complicating factor when assessing the influence of age on drug handling.…”
Section: Introduction Methodsmentioning
confidence: 99%
“…These results suggest that the younger hyperthyroid patient who smokes may achieve only a minor degree of /3-adrenoceptor blockade on conventional dosage of propranolol. The findings of higher concentrations of propranolol has lead Castleden & George (1979) to suggest that propranolol dosage should be reduced in the elderly. We feel however, that this may not be necessary.…”
Section: Introduction Methodsmentioning
confidence: 99%